"The Enemy is at Home”. The Representation of the Fifth Column during the Spanish Civil War in Nuestra Bandera Communist Newspaper - Sánchez Izquierdo, Pablo (Eikón / Imago, 2020)
During the Spanish Civil War, many artists collaborated in both sides helping in propaganda. Through the years, media like the posters have been of great interest for researchers from several fields. Nevertheless, during the conflict, the graphic illustration was also issued in other media like journals. The great number of drawings that were published in a vast quantity of newspapers requires an ambitious research but, in this paper, information about the representations in Spanish communist newspapers is offered.